Prospects for ensuring information security of business entities as a vector of their sustainable development - Topalov, Volodymyr (Global Prosperity, 2025)
Abstract. The purpose of the study is to assess the current state and identify future prospects for ensuring information security among small business entities in the context of ongoing digital transformation. In the contemporary economy, where digitalization processes are accelerating across all sectors, information security (IS) has become a critical component of business continuity and competitiveness. Small enterprises, despite being highly vulnerable to cyber threats, often lack the financial, technical, and human resources to implement comprehensive cybersecurity systems. The study applies a quantitative research methodology based on a structured questionnaire survey of small enterprises operating in the Volyn region of Ukraine. A regression model was developed to examine the relationship between IS spending and financial performance indicators of the surveyed enterprises.Results. The findings revealed that the majority of small enterprises exhibit either a low or intermediate level of information security. Key weaknesses include insufficient investment in cybersecurity infrastructure, limited implementation of preventive measures, and the absence of dedicated staff or external experts responsible for IS. Despite this, enterprises that invest more consistently in IS measures tend to demonstrate higher revenue levels, indicating a positive and statistically significant correlation.Practical implications. The study proposes an adaptive model of IS strategy for small businesses, which includes typological classification based on current IS levels and tailored strategic recommendations. This model provides practical tools for decision-makers and can serve as a foundation for both enterprise-level planning and the development of regional or national support programs.Value / originality. The scientific novelty of this research lies in the formalization of the link between information security maturity and financial performance in the small business segment, along with the development of a typology of enterprises by IS level. This contributes to the broader understanding of cybersecurity management within small enterprises under digital transformation pressures.